Analysis tools to quantify dissemination of pathology in zebrafish larvae - Stirling, David R. (Sci Rep, 2020)
We describe new open source software called QuantiFish for rapid quantitation of fluorescent foci in zebrafish larvae, to support infection research in this animal model. QuantiFish extends the conventional measurements of bacterial load and number of bacterial foci to include measures for dissemination of infection. These are represented by the proportions of bacteria between foci and their spatial distribution. We showcase these measures by comparison of intravenous and hindbrain routes of Mycobacterium marinum infection, which are indistinguishable by measurement of bacterial load and not consistently differentiated by the number of bacterial foci. The intravenous route showed dose dependent dissemination of infection, reflected by increased spatial dispersion of bacteria and lower proportions of bacteria distributed across many foci. In contrast, hindbrain infection resulted in localised disease, limited to a smaller area and higher proportions of bacteria distributed across fewer foci. The application of QuantiFish may extend beyond models of infection, to study other pathologies such as metastatic cancer.